Silibinin alleviates intestinal inflammation via inhibiting JNK signaling in Drosophila - Yan, La; Zhou, Juanyu; Yuan, Lu; Ye, Jinbao; Zhao, Xudong; Ren, Gang; Chen, Haiyang (Frontiers in Pharmacology, 2023)
Inflammatory bowel diseases (IBDs) are characterized by chronic relapsing intestinal inflammation that causes digestive system dysfunction. For years, researchers have been working to find more effective and safer therapeutic strategies to treat these diseases. Silibinin (SIL), a flavonoid compound extracted from the seeds of milk thistle plants, possesses multiple biological activities and is traditionally applied to treat liver diseases. SIL is also widely used in the treatment of a variety of inflammatory diseases attributed to its excellent antioxidant and anti-inflammatory effects. However, the efficacy of SIL against IBDs and its mechanisms remain unclear. In this study, using Drosophila melanogaster as a model organism, we found that SIL can effectively relieve intestinal inflammation caused by dextran sulfate sodium (DSS). Our results suggested that SIL supplementation can inhibit the overproliferation of intestinal stem cells (ISCs) induced by DSS, protect intestinal barrier function, acid-base balance, and intestinal excretion function, reduce intestinal reactive oxygen species (ROS) levels and inflammatory stress, and extend the lifespan of Drosophila. Furthermore, our study demonstrated that SIL ameliorates intestinal inflammation via modulating the c-Jun N-terminal kinase (JNK) signaling pathway in Drosophila. Our research aims to provide new insight into the treatment of IBDs.